Educação e barbárie - a escola e os direitos humanos no enfrentamento à intolerância - Moraes, Larissa Messias (2015)
Since the dawn of the Greek ascension, the barbarian figure retraces back to ancient times in the Western imagination. Consecutively, over the centuries and until present days, the idea of barbarism figures amid the social language, being associated with different meanings in each event and context. Recognizing the range of possible theoretical analyses, we chose to focus on barbarism as a denial mechanism of alterity, such as indifference and intolerance, and that it comes out with acts of discrimination and violence. We found great help in the ‘Critical Theory’ to build this concept of barbarism, especially with the contribution of Theodor Adorno, Walter Benjamin and Axel Honneth. Adorno’s view particularly leads us to seek in education a way to confront these denial mechanisms as an attempt to provide a society where justice, equality and valorization of diversity prevail. However, Adorno points out that only an education for the emancipation of its individuals supported by human rights, could achieve that. Thus, we seek in laws, plans, principles and researches on the Brazilian education, elements that could show us if our current education system has acted in order to perpetuate intolerance and oppression in our society, or if it has been directed towards this emancipation formation, getting through the critical formation and awareness of their individual about human rights, reversing the mechanisms that lead to barbarism.